Attitudes Of Professors Institutes Of Science And Technical Of Physical And Sports Activities At University Of Souk Ahras Towards E-learning According Some Variables - Bensayah, Samir (Université de M'sila, 2019)
The objective of this study was to know the attitudes of teachers at the institutes of science and technical of physical and sports activities in Souk Ahras university towards the electronic teaching and the differences of visions which are influenced by the variables: sex, Department Belonging, specialty, Scientific qualification, professional experience, and computer training. The study followed the descriptive method. The researcher distributes a questionnaire about a group of 24 teachers who work in the Institute selected by chance. And was treated statistically using the software (spss), and resulted in the following results: - Positive attitudes towards e-learning. - There are no differences, statistically significant, in the average of attitudes influenced by: Gender, Specialty, Scientific Qualification, Work Experience, and Computer Training تهدف هذه الدراسة الى التعرف على اتجاهات أساتذة معهد علوم و تقنيات النشاطات البدنية و الرياضية نحو التعليم الالكتروني والفروق بينهم وفق متغيرات الجنس، قسم الانتماء، التخصص، المؤهل العلمي، الخبرة المهنية، والتكوين في مجال الاعلام الآلي، لذلك تم توظيف المنهج الوصفي التحليلي لملائمته طبيعة الموضوع. وظف الباحث استمارة الاتجاه نحو التعليم الالكتروني و المكونة من 24 عبارة وزعت على عينة تكونت من 24 أستاذ اختيرت عشوائيا من بين الأساتذة الذين يدرسون بمعهد علوم و تقنيات النشاطات البدنية والرياضية بجامعة سوق أهراس، وعولجت البيانات احصائيا باستخدام برنامج spss. توصلنا الى أن للأساتذة اتجاهات ايجابية نحو التعليم الالكتروني، كما لا توجد فروق دالة احصائية عند مستوى (0.05) في اتجاهاتهم نحو التعليم الالكتروني تعزى لمتغيرات الجنس، التخصص، المؤهل العلمي، والخبرة المهنية و التكوين في مجال الاعلام الآلي.
Keywords: Attitudes –Professors- e-learning - some variables.